A qualitative exploration of the relationship between race and identity in Durban, Greenwood Park: A social constructionist perspective - Prinsloo, Laurelle (The IIE, 2020)
This study sought to explore the relationship between race and identity with particular focus on Coloured people’s subjective experiences regarding race and identity. Insufficient acknowledgement of the role Coloured people have on reconstructing and creating their identity within an intermediate social position has been highlighted in the literature. Using three participants, qualitative semi-structured interviews were conducted to gain an indepth understanding by exploring the subjective perspective of race and identity. Findings revealed three major themes that were critical in the relationship between race and identity; historical context, power dynamics and social construction and, political and social transformation. The results show that the past is still presently reflected in identities in terms of race; power dynamics and social construction is an influential factor in social aspects which create identity and race; that participants actively attempt to transform their identity into one’s own making and construct alternative perceptions. Power/political dynamics relates to the historical dynamics which still come into play regarding race and identity. The large literature on Western Cape Coloured’s poses limitation for the research on Durban Coloured’s. It is recommended that changes should be geared towards understanding the subjective Durban, Coloured perspective of identity formation through personal experiences.
Keywords: Race and identity; Social constructivism; Durban; South Africa